Teori Jean Piaget vs Lev Vygotsky dalam Perkembangan Anak di Kehidupan Bermasyarakat - Habsy, Bakhrudin All; Malora, Popo Indra; Widyastutik, Dwi Rahayu; Anggraeny, Trya Ayu (Lembaga Yasin AlSys, 2024)
Child development in the context of social life is a complex and important topic in developmental psychology. Two theories that have greatly influenced the understanding of children's development in social settings are those of Jean Piaget and Lev Vygotsky. Jean Piaget's theory explains the urgency of the role of cognition in children's development. Piaget describes children constructing their own knowledge through stages of cognitive development. In the context of social life, Piaget's theory highlights how children acquire and adapt knowledge through interaction with their social environment. Children learn by exploring, asking questions, and building knowledge with peers and adults. Meanwhile, Lev Vygotsky emphasized the role of the social environment in children's development. His theory introduced the concept of real developmental fields, where children can learn from interactions with more experienced people. In social life, Vygotsky suggested that children can develop cognitive and social skills through cooperation with adults and peers. This reinforces the idea that learning is a social process that takes place in a social context. The combination of Piaget and Vygotsky's theories helps us understand how children develop an understanding of their social world and how the social environment plays an important role in this process. Through purposeful exploration and interaction in community life, children can build the foundation of social knowledge and skills needed to thrive and become contributing members of society.